Characterisation of asthma subgroups associated with circulating YKL-40 levels. Issue 4 (12th October 2017) - Gomez, Jose L.; Yan, Xiting; Holm, Carole T.; Grant, Nicole; Liu, Qing; Cohn, Lauren; Nezgovorova, Vera; Meyers, Deborah A.; Bleecker, Eugene R.; Crisafi, Gina M.; Jarjour, Nizar N.; Rogers, Linda; et al.
The chitinase-like protein YKL-40 mediates airway inflammation and serum levels are associated with asthma severity. However, asthma phenotypes associated with YKL-40 levels have not been precisely defined. We conducted an unsupervised cluster analysis of asthma patients treated at the Yale Center for Asthma and Airways Disease (n=156) to identify subgroups according to YKL-40 level. The resulting YKL-40 clusters were cross-validated in cohorts from the Severe Asthma Research Programme (n=167) and the New York University/Bellevue Asthma Repository (n=341). A sputum transcriptome analysis revealed molecular pathways associated with YKL-40 subgroups. Four YKL-40 clusters (C1–C4) were identified. C3 and C4 had high serum YKL-40 levels compared with C1 and C2. C3 was associated with earlier onset and longer duration of disease, severe airflow obstruction, and near-fatal asthma exacerbations. C4 had the highest serum YKL-40 levels, adult onset and less airflow obstruction, but frequent exacerbations. An airway transcriptome analysis in C3 and C4 showed activation of non-type 2 inflammatory pathways. Elevated serum YKL-40 levels were associated with two distinct clinical asthma phenotypes: one with irreversible airway obstruction and another with severe exacerbations. The YKL-40 clusters are potentially useful for identification of individuals with severe or exacerbation-prone asthma. Asthma with high serum YKL-40 levels is associated with severe lung function impairment and severe exacerbations http://ow.ly/wyly30elajo